2018
DOI: 10.1515/pp-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns, attitudes, and knowledge among physicians regarding cytoreductive surgery and HIPEC for patients with peritoneal metastases

Abstract: BackgroundCytoreductive surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC) is a treatment option for patients with peritoneal metastases shown to provide improved overall survival for appropriately selected patients. However, the availability and utilization of this treatment remains limited. The aim of this survey-based study was to evaluate factors influencing physician treatment choices for peritoneal metastases.MethodsSurveys were mailed to medical oncologists and surgeons in Virginia, Maryland,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…While the incidence continues to increase, access to PSM experts remains limited, with many CRS/HIPEC centers located in academic institutions due to its inherent complexity and investigational nature for some primaries 7‐9 . This leads to insufficient referrals of patients who desperately need treatment 10 …”
Section: Introductionmentioning
confidence: 99%
“…While the incidence continues to increase, access to PSM experts remains limited, with many CRS/HIPEC centers located in academic institutions due to its inherent complexity and investigational nature for some primaries 7‐9 . This leads to insufficient referrals of patients who desperately need treatment 10 …”
Section: Introductionmentioning
confidence: 99%
“…However, our response rate of 36.2% is much higher that other similar international surveys in this field [12,13,46]. Furthermore, while most other surveys [12,13,47,48] have assessed clinician views and awareness on effectiveness and safety of CRS and HIPEC, our survey and a recent Swiss survey [46] served to evaluate how clinicians view and manage commonly encountered cases with peritoneal disease, as timely, appropriate and evidence based care in such cases translates to better clinical outcomes. While this survey covered the use of HIPEC, it failed to evaluate the role of other intraperitoneal chemotherapy modalities such as early postoperative intraperitoneal chemotherapy (EPIC) or pressurised aerosolised chemotherapy (PIPAC).…”
Section: Discussionmentioning
confidence: 87%
“…However, it is unclear whether skepticism is due to lack of awareness and knowledge among clinicians in the management of peritoneal disease. Recent studies have shown that poor awareness of the value of the CRS and HIPEC in the management of colorectal peritoneal metastases (CRPM) contributes to reduced utilisation of CRS and HIPEC [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Limited adoption and access of CRS/HIPEC for patients underlines the scepticism among the clinicians about its role and efficacy despite mounting evidence. Poor knowledge of procedure and benefit is one of the most important reasons for underutilization [ 13 ], [ 16 ], [ 17 ]. This procedure is technically challenging with high morbidity and mortality, needing an institutional setup with well-equipped OT, anaesthetic and intensive care departments.…”
Section: Discussionmentioning
confidence: 99%